Thermographic Imaging of the Superficial Temperature in Racing Greyhounds before and after the Race - Mari Vainionpää; Esa-Pekka Tienhaara; Marja Raekallio; Jouni Junnila; Marjatta Snellman; Outi Vainio (The Scientific World Journal)
A total of 47 racing greyhounds were enrolled in this study on two race days (in July and September, resp.) at a racetrack. Twelve of the dogs participated in the study on both days. Thermographic images were taken before and after each race. From the images, superficial temperature points of selected sites (tendo calcaneus, musculus gastrocnemius, musculus gracilis, and musculus biceps femoris portio caudalis) were taken and used to investigate the differences in superficial temperatures before and after the race. The thermographic images were compared between the right and left legs of a dog, between the raced distances, and between the two race days. The theoretical heat capacity of a racing greyhound was calculated. With regard to all distances raced, the superficial temperatures measured from the musculus gastrocnemius were significantly higher after the race than at baseline. No significant differences were found between the left and right legs of a dog after completing any of the distances. Significant difference was found between the two race days. The heat loss mechanisms of racing greyhounds during the race through forced conduction, radiation, evaporation, and panting can be considered adequate when observing the calculated heat capacity of the dogs.